2012
DOI: 10.5114/jcb.2012.32559
|View full text |Cite
|
Sign up to set email alerts
|

Physics Contributions Dosimetric impact of point A definition on high-dose-rate brachytherapy for cervical cancer: evaluations on conventional point A and MRI-guided, conformal plans

Abstract: PurposeTo investigate the dosimetric impact of point A definitions on both conventional point A plans and MRI-guided conformal high-dose-rate (HDR) brachytherapy plans.Material and methodsFifty-five HDR plans of 36 patients with FIGO stage I to IV cervical cancer were retrospectively studied; these included 30 conventional treatments and 25 conformal plans. Two different point A definitions were explored: the revised Manchester point A and the new point A as recommended by the American Brachytherapy Society. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…A T&O applicator was reconstructed (digitized) on T1‐weighted MR images 6. The details of the HDR workflow, imaging, and planning have been previously described 21, 22, 23, 24…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A T&O applicator was reconstructed (digitized) on T1‐weighted MR images 6. The details of the HDR workflow, imaging, and planning have been previously described 21, 22, 23, 24…”
Section: Methodsmentioning
confidence: 99%
“…The hybrid‐inverse optimization process21, 22, 25, 26 includes three main steps: (a) generate a conventional Point A plan, (b) set dose‐volume objective constraints for inverse optimization based upon the resulting DVH parameters, and (c) perform final dose shaping using graphical optimization based upon DVH parameters and isodose lines. As a last step, a physician reviews the isodose lines for each slice on coronal, sagittal, and axial views.…”
Section: Methodsmentioning
confidence: 99%
“…This algorithm established a set of dosimetric constraints on the four reference lines based upon its prescription dose (two bilateral lines parallel to the tandem and a lateral line parallel to each ovoid, which will be described in detail for Case B in the Materials & Methods section E.2 below). Hereafter, Point A‐based T&O plans refer to the plans generated this way, the details of which are described by Anderson et al (35) These clinical Point A based T&O plans were exported from the legacy version of the TPS and then imported into the upgraded TPS (version 6.5). Applicator geometry, 3D imaging datasets, and dose constraints for each reference line were kept the same while using different versions of the inverse planning routine.…”
Section: Methodsmentioning
confidence: 99%
“…By delivering a substantially high dose to the tumor in the central pelvis, while sparing the nearby organs at risk due to the rapid dose falloff, (13) BT leads to an improvement in the patient survival rate with a decrease in the recurrence rate. (9,14–16) Throughout the abundant clinical experience accumulated by radiation oncologists, delivery of a certain dose to point A is still a commonly used prescription for cervical cancer BT 17 , 18 , 19 . Traditionally, the treatment planning is performed through the reconstructed dummy seed positions within the applicators and the prescribed point doses from two orthogonal film images, (5) in which the isodose lines passing through point A form a pear shape encompassing the intended boost treatment volume (20) …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zhang et al (29) reported that a 9 mm shift in point A can cause a 14% dose rate difference for low‐dose‐rate brachytherapy. Therefore, to obtain the correct location of point A for each individual treatment is extremely important, since a slight variation of its location can result in significant dose variation 17 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%